2021
DOI: 10.3389/fphy.2021.651808
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in Cubic A15-type V–Nb–Mo–Ir–Pt High-Entropy Alloys

Abstract: We report the crystal structure and superconducting properties of new V5+2xNb35−xMo35−xIr10Pt15 high-entropy alloys (HEAs) for x in the range of 0 ≤x≤ 10. These HEAs are found to crystallize in a cubic A15-type structure and have a weakly coupled, fully gapped superconducting state. A maximum Tc of 5.18 K and zero-temperature upper critical field Bc2(0) of 6.4 T are observed at x = 0, and both quantities decrease monotonically with the increase of V content x. In addition, Tc shows an increase with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In general, high levels of disorder in crystalline superconductors limit the formation of Cooper pairs, partly due to a decrease in state density or an increase in effective Coulomb repulsion between paired electrons. [ 12,13 ] It has been reported that HEA superconductors exist in bcc‐, [ 2,3,14–22 ] α‐Mn‐, [ 23 ] β‐Mn, [ 24 ] hcp‐, [ 25–27 ] CsCl‐, [ 28,29 ] A15‐type [ 30–32 ] and σ‐phase [ 33,34 ] structures. Additionally, high‐entropy superconductors' superconducting transition temperature ( T c ) are robust against physical pressure and show a certain correlation with valence electron count (VEC).…”
Section: Introductionmentioning
confidence: 99%
“…In general, high levels of disorder in crystalline superconductors limit the formation of Cooper pairs, partly due to a decrease in state density or an increase in effective Coulomb repulsion between paired electrons. [ 12,13 ] It has been reported that HEA superconductors exist in bcc‐, [ 2,3,14–22 ] α‐Mn‐, [ 23 ] β‐Mn, [ 24 ] hcp‐, [ 25–27 ] CsCl‐, [ 28,29 ] A15‐type [ 30–32 ] and σ‐phase [ 33,34 ] structures. Additionally, high‐entropy superconductors' superconducting transition temperature ( T c ) are robust against physical pressure and show a certain correlation with valence electron count (VEC).…”
Section: Introductionmentioning
confidence: 99%